Attenuation imaging as a new ultrasonographic application for identifying placental haematoma. Issue 3 (2nd March 2021) - Yamaguchi, Masahiro; Umazume, Takeshi; Noshiro, Kiwamu; Watari, Hidemichi
Abstract : We present a case in which attenuation imaging (ATI), a recently developed ultrasonographic application, facilitated the diagnosis of preplacental and postplacental haematoma. Placental abruption is a serious condition that affects the prognosis of infants and is difficult to diagnose. Ultrasonography is the primary imaging modality that complements the clinical findings in the diagnosis; however, its sensitivity is low, and improved diagnostic accuracy is desired. Here, we found that placental haematomas on the placental fetal surface observed at 19 weeks of gestation were indistinct from placental parenchyma in B-mode ultrasonographic imaging. In ATI, the placental parenchyma was colour-mapped, but the haematoma portion was not, which helped identify the haematoma. ATI, which also colour-maps uniform tissues, did not colour-map vessels within the placenta. ATI has a breakthrough potential for improving the diagnosis of placental abruption.